2012
DOI: 10.1039/c2fd20029e
|View full text |Cite
|
Sign up to set email alerts
|

Arrested coalescence of viscoelastic droplets with internal microstructure

Abstract: There are many new approaches to designing complex anisotropic colloids, often using droplets as templates. However, droplets themselves can be designed to form anisotropic shapes without any external templates. One approach is to arrest binary droplet coalescence at an intermediate stage before a spherical shape is formed. Further shape relaxation of such anisotropic, arrested structures is retarded by droplet elasticity, either interfacial or internal. In this article we study coalescence of structured dropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
182
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(193 citation statements)
references
References 33 publications
(45 reference statements)
10
182
0
1
Order By: Relevance
“…Previous work showed that droplets containing an elastic network of crystals can initiate but not finish coalescence, creating a range of anisotropic intermediate droplet shapes, [1,10] but only recently has a physical model of the process for uniform [7] and non-uniform [8] droplet pairs been developed. Essentially the interfacial pressure driving two droplets to minimize their area must be offset by the internal elasticity to stably arrest coalescence at an intermediate state: a liquid doublet rather than a sphere.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work showed that droplets containing an elastic network of crystals can initiate but not finish coalescence, creating a range of anisotropic intermediate droplet shapes, [1,10] but only recently has a physical model of the process for uniform [7] and non-uniform [8] droplet pairs been developed. Essentially the interfacial pressure driving two droplets to minimize their area must be offset by the internal elasticity to stably arrest coalescence at an intermediate state: a liquid doublet rather than a sphere.…”
Section: Introductionmentioning
confidence: 99%
“…Essentially the interfacial pressure driving two droplets to minimize their area must be offset by the internal elasticity to stably arrest coalescence at an intermediate state: a liquid doublet rather than a sphere. [7] In such cases the exact doublet shape represents one of a number of intermediate points between the beginning state of two discrete droplets and a completely coalesced single sphere and is determined by the level of solids in the droplet and the point at which coalescence is arrested. [7] We extend that work here by examining the dynamic behavior of an aggregate of three arrested droplets, a triplet, as multiple connections are the basis for many fluid microstructures formed during the manufacture of food, coatings, and material templates like bijels.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations